AN ANALYSIS OF APHASIA LANGUAGE DISORDER TOWARD ADULT: A PSYCHOLINGUISTIC STUDY. (The GIST, 2022)
Aphasia is analysed in this research because this topic become one of the theory that include to the language and the brain. The aims of this research is to define language disorder toward adult in a certain cause which refers to aphasia. To support this research, the writer used the theory of language disorder by Vasic (2006).  The methodology that used by the writer is descriptive qualitative. The data of this research were analysed by using Vasic’s theory about language disorder. In the process to get the data, the writer chooses YouTube media as the source and the object of this research is a patient of aphasia namely Michelle, 17 years old. She got a Stroke that happened in February 27, 2011 from long boarding / snowboarding incident which made her experienced the difficulty to used language, she cannot speak clearly because of the disease. From the result of analysing, the writer found that Michelle experienced the intact of comprehension, her fluency is affected and her repetition also naming a thing is slightly affected. The writer biggest wished is this research will enrich the reader knowledge about language disorder particularly aphasia. Keywords: Language Disorder, Aphasia, psycholinguistic.